Junk APEC! - Dongeto, Rom.; Libres, Bedette
A documentary on the people's struggle against APEC and globalization; it also features the People's Conference Against Imperialist Globalization and the People's Caravan, both held to coincide with the 1996 APEC Leaders' Summit in the Philippines.
Keywords: Public administration; International relations